Pengaruh Metode SQ3R Terhadap Hasil Belajar Bahasa Indonesia Kelas IV SD Negeri 102083 Pabatu - Fince Putri Yeni Purba; Suryana Rajagukguk; Elly Prihasti Wuriyani; Wisman Hadi (LP3M KH Yazid Karimullah Institute, 2024)
This research aims to determine the significant differences in learning outcomes between students who follow the SQ3R learning method and students who follow conventional learning. This type of research is a quasi-experiment with a nonequivalent control group design. The sampling technique used is a random sampling technique. The research sample was 72 students. The method for collecting data on reading skills uses multiple choice tests. The data obtained were analyzed using parametric statistical techniques, namely the t-test. The results of data analysis show that there are significant differences in reading skills between students who study using the SQ3R learning method and students who study using conventional learning in class IV of SD Negeri 102083 Pabatu. Learning innovation using the SQ3R learning method can be used as an alternative to improve student learning outcomes in Indonesian language subjects.